Influence of Non-invasive Ventilation in an Adult Patient With Acute Epiglottitis: a Case Report - Bamadhaf, Wail [UNESP]; AlRahma, Ali [UNESP]; Ali, Khalid [UNESP]; Hamoud, Khaled [UNESP] (Cureus Inc, 2022)
Adult acute epiglottitis is a rare, life-threatening disease that requires prompt airway management, resuscitation, and stabilization. This case report discusses a patient with type Iota Iota respiratory failure due to acute epiglottitis, which was managed successfully with non-invasive positive-pressure ventilation in the emergency department.We report a case of a male patient in his 30s who arrived at the emergency department complaining of sore throat, cough, and shortness of breath. He was found to be in severe respiratory distress. The patient's condition improved dramatically after non-invasive positive-pressure ventilation, which prevented the need for endotracheal intubation. He was admitted to the ICU and discharged without complications five days later.Non-invasive positive-pressure ventilation may help manage moderate cases of acute epiglottitis with partial airway obstruction as a bridging therapy until other treatments have decreased edema, thus preventing the need for endotracheal intubation.
Keywords: non-invasive ventilation; type ?? respiratory failure; adult epiglottitis; case report; non-invasive mechanical ventilation